PENINGKATAN KEMAMPUAN TENAGA PENGAJAR ROBOTIK LPK UNIK ROBOT MENGGUNAKAN TEKNOLOGI TEPAT GUNA DAN PEMASARAN - Indriyanto, Jatmiko; Purwono, Purwono; Hermanto, Nandang (Jurnal Locus Penelitian dan Pengabdian, 2023)
This research includes community service which aims to improve the skills of robotics teachers in Purwokerto, Banyumas Regency. UNIK ROBOT, a robotics education institution, has partnered with schools in the area to provide robotics education through extracurricular activities. Interest in robotics from schools and students is very high, because technology and robotics increasingly dominate everyday life. Project-based education methods and action learning are the main focus, with the aim of developing 21st century skills, such as creativity, critical thinking, communication and collaboration. Evaluation of success was carried out through observation methods, oral tests, and questionnaires, which showed a significant increase in robotics and online marketing skills by 90%. It is hoped that this activity can become the basis for further development of robotics education in Purwokerto and its surroundings. The results of the research stated that educational activities for robotics teachers in Purwokerto succeeded in increasing robotics and online marketing skills by 90%. Hopefully in the future there will be robotic material that can be taught again so that learning activities can further develop.